Continuation of pregnancy after first‐trimester exposure to mifepristone: an observational prospective study. Issue 5 (24th January 2013) - Bernard, N; Elefant, E; Carlier, P; Tebacher, M; Barjhoux, CE; Bos‐Thompson, MA; Amar, E; Descotes, J; Vial, T
<x xml:space="preserve">Abstract</x> Objective To report the follow‐up of continuing pregnancies after first‐trimester exposure to mifepristone. Design Observational prospective study. Setting France. Sample Patients exposed to mifepristone during the first 12 weeks of pregnancy. Methods Women were included in the study when they or their doctors asked a French pharmacovigilance centre or the Paris Teratogen Information Service about the risk of mifepristone exposure in early pregnancy. Exclusion criteria were requests received after 22 weeks of gestation or subsequent elective termination of pregnancy without a pathological examination of the fetus. Data on maternal history and drug exposure were collected on first contact, and pregnancy outcomes were documented at follow‐up. Main outcome measures Rate of major congenital malformations. Results A total of 105 pregnancies were included, with 46 exposed to mifepristone alone, and 59 exposed to both mifepristone and misoprostol. There were 94 live births (90.4%) and 10 (9.6%) miscarriages (including one with major malformation). Elective termination of pregnancy was performed after the subsequent diagnosis of trisomy 21 in one case. The overall rate of major congenital malformations was 4.2% (95% CI 1.2–10.4%), with two cases among 38 patients exposed to mifepristone alone, and two cases among 57 patients exposed to both mifepristone and misoprostol. Conclusions This first prospective study found that the rate of major malformations after first‐trimester exposure to mifepristone is only slightly higher than the expected 2–3% rate in the general population. Such findings provide reassuring data for risk evaluation for continuation of pregnancy after mifepristone exposure.